2005
DOI: 10.1128/cdli.12.8.1006-1009.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microcapillary Cytometry Technology and Flow Cytometry for CD4 + and CD8 + T-Cell Estimation

Abstract: An alternative technology for the estimation of T cells based on a microcapillary technique (Guava Technologies, Hayward, CA) was compared to FACSCount (Becton Dickinson, San Jose, CA). Samples from 51 human immunodeficiency virus-infected and 21 healthy individuals were tested. The correlation (r) of the two systems for CD4؉ T cells was 0.994, and the coefficient of variation was 6.5%, establishing equable performance between the two technologies.The number of human immunodeficiency virus (HIV)-infected indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 5 publications
(1 reference statement)
1
13
0
Order By: Relevance
“…We had earlier analysed the correlation of the CD4 + T cells estimated by the GuavaEasy CD4 system and the ß ow cytometry and had shown that both systems are usable interchangeably as there was a very signiÞ cant correlation. [5] The CD4 + T cells and CD3 + cell values of the all the quality control samples were within the expected acceptable range. In the present study, we have also analysed the association of CD4 + T cell estimated by GuavaEasyCD4 system and the viral load level estimated by artus HIV-1 RG RT-PCR assay and found to be signiÞ cant (r = −0.55).…”
Section: It Is Reported That the Mean Cd4mentioning
confidence: 93%
See 2 more Smart Citations
“…We had earlier analysed the correlation of the CD4 + T cells estimated by the GuavaEasy CD4 system and the ß ow cytometry and had shown that both systems are usable interchangeably as there was a very signiÞ cant correlation. [5] The CD4 + T cells and CD3 + cell values of the all the quality control samples were within the expected acceptable range. In the present study, we have also analysed the association of CD4 + T cell estimated by GuavaEasyCD4 system and the viral load level estimated by artus HIV-1 RG RT-PCR assay and found to be signiÞ cant (r = −0.55).…”
Section: It Is Reported That the Mean Cd4mentioning
confidence: 93%
“…[5] The CD4 evaluation in our laboratory by this instrument is a part of a regular external quality assurance program carried out by WHO and a laboratory in Thailand under the auspices of NACO, India. The HIV-1 viral load was estimated using real-time PCR, RotorGene 3000 (Corbet Research ScientiÞ c, Australia) with artus HIV-1 RG RT-PCR assay (Qiagen GmbH, Germany).…”
Section: Absolute Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…The CD4 ϩ T-cell counts were estimated with the Guava EasyCD4 System (Guava Technologies, Hayward, CA) as reported earlier (12). The HIV-1 load was estimated using real-time PCR equipment (Rotor Gene 3000; Corbett Research Scientific, Australia) with reagents form Artus (Qiagen, GMBH, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…[3] Previous reports from India have reported M184V Technologies, Hayward, CA, USA), as described earlier, was used for CD4 estimation. [6] Viral load estimation was done using Artus RealArt™ HIV-1 kits (Qiagen Hamburg Gmbh, Germany) using Rotor-Gene™ 3000. [7] The genotypic resistance assay was carried out by sequencing the Pr and RT genes.…”
Section: Introductionmentioning
confidence: 99%